Researchers perceptions of DH trends and topics in the English and Spanish-speaking community : DayofDH data as a case study - Rio Riande, María Gimena del (2016)
Defining the state of the art in Digital Humanities (DH) is a really challenging task, given the range of contents that this tag covers. One of the most successful efforts in this sense has been the international blogging event known as DayofDH or A Day in the Life of the Digital Humanities project, promoted and sponsored by centerNet ( http://www.dhcenternet.org/), which has put together digital humanists from around the world to document once a year what they do (Rockwell et al., 2012). The websites of DayofDH were hosted in North America until 2015, when it was coordinated in Europe by LINHD ( http://linhd.uned.es), the Digital Innovation Lab, at UNED in Madrid. Participants belong to several countries around the world.The relevance of DH in non-English speaking countries has been quick and important in the last decade, and especially important in the Spanish-speaking world (Spence and González-Blanco, 2014; González-Blanco, 2013; Del Rio Riande, 2014a; Del Rio Riande, 2014b; Galina et al., 2015). Technological projects for humanities have existed in the Spanish world for many years; however, the discipline called "Digital Humanities" arose in 2011 with the first meeting that originated the Spanish Digital Humanities Association, HDH. This relevance is reflected in the creation of a parallel version of the DayofDH in Spanish, the DíaHD, which was hosted by the UNAM in Mexico in 2013 and 2014 and converged in the last initiative at UNED transforming both blogging events into a bilingual version of the Day.